Comparative Analysis of the α-Like Globin Clusters in Mouse, Rat, and Human Chromosomes Indicates a Mechanism Underlying Breaks in Conserved Synteny - Tufarelli, Cristina; Hardison, Ross; Miller, Webb; Hughes, Jim; Clark, Kevin; Ventress, Nicki; Frischauf, Anna Maria; Higgs, Douglas R. (Genome Research, 2004)
We have sequenced and fully annotated a 65,871-bp region of mouse Chromosome 17 including the Hba-ps4 α-globin pseudogene. Comparative sequence analysis with the functional α-globin loci at human Chromosome 16p13.3 and mouse Chromosome 11 shows that this segment of mouse Chromosome 17 contains a group of three α-like pseudogenes (Hba-psm–Hba-ps4–Hba-q3), similar to the duplicated sets found at the functional mouse cluster on Chromosome 11. In addition, exons 7 to 12 of the mLuc7L gene are present just downstream from the pseudogene cluster, indicating that this clone contains the region in which human 16p13.3 switches in synteny between mouse Chromosomes 11 and 17. Comparison of the sequences around the α-like clusters on the two mouse chromosomes reveals the presence of conserved tandem repeats. We propose that these repetitive elements have played a role in the fragmentation of the mouse α cluster during evolution.
10.1101/gr.2143604